From Centralized Authority to Shared Vision: Collective-Transformational Leadership in Pesantren - Sutrisno Sutrisno; Ethem Gürhan; Muhtar Hazawawi (LPPPM STAI Darul Hikmah Bangkalan, 2026)
The sustainability of faith-based educational organizations often relies heavily on the singular charisma of their founders, making them highly vulnerable to institutional collapse upon the founder's demise (